Study on the influence of the magnetron power supply on the properties of the Silicon Nitride films - Kiseleva D. V. Darjya Vasiljevna; Yuriev Yu. N. Yuri Nikolaevich; Petrakov Yu. V. Yury Vyacheslavovich; Sidelev D. V. Dmitry Vladimirovich; Korzhenko D. V. Dmitry Vladimirovich; Erofeev E. V. Evgeny Viktorovich (2017, 2017)
Title screen